Avaliação histométrica do processo de reparo em defeitos de calvária de ratos com membrana de PCL e membrana de colágeno porcino - Francati, Tamires Melo [UNESP] (2017)
The use of membranes that help in the process of guided bone regeneration (GBR) is also an aspect of the study of biomaterials compatible that assist in the process of repair. Still in a study phase membrane developed at the University of San Carlos is based on nano polycaprolactone (PCL) fibers which is a biodegradable polymer with a rhythm is controllable degradation, maintaining the structure during a longer period of cell growth. The objective of this project was to evaluate by means of histological analysis the potential to aid in bone neoformation PCL membrane with 5% of HA and porcine membrane in the process of critical bone defects repair in rat calvarium. 36 rats were used for histological analysis of critical defects in rat calvarium in times of 7, 30 and 60 days divided into three groups: G1: Blood clot, G2: Porcine embrane, G3: PCL. Histological analysis showed that the PCL membrane has a biological behavior with the fabric since it was not verified foreign body reaction in any specimen, it was also possible to verify that it allowed the GBR occurred both to 30 about the 60 days, and in some specimens it was verified the complete closure of the defect. The PCL membrane proved to be biocompatible with the potential to assist in the processes of GBR